2011
DOI: 10.1089/lap.2010.0515
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Early Outcomes of Intracorporeal and Extracorporeal Gastroduodenostomy After Laparoscopic Distal Gastrectomy for Gastric Cancer

Abstract: TLDG with intracorporeal gastroduodenostomy is as safe and feasible as LADG for patients with gastric cancer. Moreover, TLDG is less invasive and more comfortable for patients than LADG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
32
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 14 publications
(18 reference statements)
0
32
1
Order By: Relevance
“…The results showed that the method was safe, simple and less invasive. In the comparative studies between DSG and LADG with a circular anastomosis, the majority of results showed that there was no difference in the surgical time and postoperative complication rate [1, 8, 23], and the long-term outcomes were also comparable [10]. DSG was considered to be less invasive [1, 3], especially in obese patients [8, 24].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that the method was safe, simple and less invasive. In the comparative studies between DSG and LADG with a circular anastomosis, the majority of results showed that there was no difference in the surgical time and postoperative complication rate [1, 8, 23], and the long-term outcomes were also comparable [10]. DSG was considered to be less invasive [1, 3], especially in obese patients [8, 24].…”
Section: Discussionmentioning
confidence: 99%
“…Enrolled patients with I stage GC represented more than 85 % of all patients. Patients with locally advanced GC were less common, and most of them had stage II or stage IIIA GC [5, 22, 23]. Stage IIIB and IIIC diseases were rarely reported.…”
Section: Discussionmentioning
confidence: 99%
“…With the rapid development of laparoscopic instruments and techniques, laparoscopy-assisted distal gastrectomy (LADG) can be used for AGC treatment [3]. Several retrospective studies have demonstrated that totally laparoscopic distal gastrectomy (TLDG) was safer, more feasible, and less invasive than LADG [4][5][6][7]. Additionally, Patriti et al [8] indicated that robot-assisted laparoscopic gastrectomy with D2 lymph node dissection for adenocarcinoma was feasible and safe.…”
Section: Introductionmentioning
confidence: 99%
“…When gastroduodenostomy is performed during laparoscopic surgery, extracorporeal anastomosis through mini-laparotomy has been reported to be a safe procedure. However, the benefits of intracorporeal gastroduodenostomy have been reported recently 3,4. Gastrojejunostomy can easily be performed intracorporeally with a linear stapler.…”
Section: Introductionmentioning
confidence: 99%